Mass Psychology and Social History - Semechkin N.I. (Социальная психология и общество, 2020)
Objectives. Analyze the historical process and in particular the movements of the masses not from the familiar for Russian researchers positions of famous Karl Marx’s thesis: “being determines consciousness”, but from the opposite point of view — social existence is determined by the state of public social consciousness, with the purpose to see how the transformation of social consciousness towards its decollectivization and demythologization, that creates shocking mental discomfort, generates mass social movements unconsciously seeking back in time, which predetermines the course of social history. Background. Naive-spontaneous “materialism” of ordinary consciousness, but, even more surprising, scientists’ psychologists, makes it difficult to understand the real determinants of human behavior, that is, the fact that in the basis of individual behavior, and public life, and history in general lies not politics, not economics, but social psychology, that, contrary to the well-known Lenin’s’ aphorism, politics and economics are a concentrated representation of psychology. Methodology. Theoretical analysis of socio-philosophical and psychological literature; comparative-historical analysis. Conclusions. Transformation of public consciousness initiates the creation of utopian projects oriented into the past. Utopias evoke powerful social movements of the masses, fascinated by the irrational idea of returning to the “golden age,” in paradise. Thus, the dynamics of social-historical processes are determined not by economics and politics, but by the logic of the transformation of the archaic collective consciousness in the course of its individualization and demythologization.